2022
DOI: 10.1101/2022.07.20.500724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unified model for the surveillance of translation in diverse noncoding sequences

Abstract: Translation is pervasive outside of canonical coding regions, occurring in lncRNAs, UTRs, and introns. While the resulting polypeptides are often non-functional, translation in noncoding regions is nonetheless necessary for the birth of new coding regions. The mechanisms underlying the surveillance of translation in diverse noncoding regions and how escaped polypeptides evolve new functions remain unclear. Intriguingly, noncoding sequence-derived functional peptides often localize to membranes. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…Similarly, this enrichment could reflect evolutionary pressure to avoid expression of unwanted products, balanced against the advantage of occasionally allowing novelty to emerge. The overrepresentation of TM domains, perhaps coupled with the absence of other signals, could be part of a surveillance mechanism that detects and degrades aberrant translation products, similarly to what was found in a recent preprint 20 .…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, this enrichment could reflect evolutionary pressure to avoid expression of unwanted products, balanced against the advantage of occasionally allowing novelty to emerge. The overrepresentation of TM domains, perhaps coupled with the absence of other signals, could be part of a surveillance mechanism that detects and degrades aberrant translation products, similarly to what was found in a recent preprint 20 .…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, this enrichment could reflect evolutionary pressure to avoid expression of unwanted products, balanced against the advantage of occasionally allowing novelty to emerge. The overrepresentation of TM domains, perhaps coupled with the absence of other signals, could be part of a surveillance mechanism that detects and degrades aberrant translation products, similarly to what was found in a recent preprint ( Kesner et al 2022 ).…”
Section: Discussionsupporting
confidence: 53%
“…Recent research in yeast has revealed a significant enrichment of transmembrane domains 16,22 (TMDs) within putative peptides of de novo ORFs, suggesting an association with cellular membranes. Notably, many studies identified de novo ORFs in yeast 22,59 and small nORFs in humans 14,67 that localize to diverse cellular membranes, such as ER, vacuole, endosome, or mitochondria. These findings have raised the possibility that de novo ORFs could play a role in a range of transport processes, such as ion, amino acid, and protein transport across cellular membranes.…”
Section: Discussionmentioning
confidence: 99%